Financial liberalization and its implications for private savings in sub-Saharan Africa - Elizabeth Asiedu; Fafanyo Asiseh; Theresa Mannah-Blankson; Jones Arkoh Paintsil (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
This paper employs data from 103 developing countries between 1981 and 2012 to examine the determinants of private savings in sub-Saharan Africa (SSA), with a focus on the effect of financial liberalization on private savings. It also analyses why the savings rate for SSA countries is lower than for other developing countries, by examining whether the determinants of private savings in SSA differ significantly from non-SSA countries. We find: (i) financial liberalization does not have a significant effect on private savings in all countries; (ii) the private savings rate for SSA countries is similar to non-SSA countries, after controls for relevant determinants of private savings; (iii) private savings are persistent, but the degree of persistence is lower for SSA countries; (iv) public savings crowd out private savings, but the crowding-out is more severe in SSA countries; (v) the growth rate of income per capita has a significant and positive effect on personal savings in both country groups; (vi) the effect of financial liberalization on private savings is similar for SSA countries in a monetary union and SSA countries outside a monetary union.
Keywords: O16; O19; O23; O55; 330; developing countries; financial liberalization; monetary unions; private savings; subSaharan Africa